Analisis Peran Sistem Informasi Dalam Meningkatkan Efektivitas Pengendalian Persediaan Barang Dagang Pada PT. Mayora Indah Tbk - Ristayanti Seftyananta; Imelia Shalshabilla; Rendy Ainur Rachmawan; Dwi Ermayanti Susilo (LPPM UBSI Kampus Kota Tegal, 2024)
This research aims to examine the role of information system analysis in enhancing the effectiveness of inventory control of consumer goods at PT Mayora Indah Tbk. As a leading consumer goods company in Indonesia, PT Mayora Indah Tbk faces complex challenges in inventory management to ensure timely and optimal availability of goods. In this context, information system analysis is considered a key approach to identify, evaluate, and improve existing inventory control processes. This study adopts a qualitative approach by conducting a review of the information systems used by PT Mayora Indah Tbk for inventory management. Data is collected through interviews with key personnel, direct observations, and analysis of relevant documents. The research findings highlight the importance of integrating information systems to strengthen inventory control, including the use of information technology for real-time monitoring, inventory tracking, and demand forecasting. By combining advanced information technology with effective inventory management practices, PT Mayora Indah Tbk can enhance accuracy, efficiency, and transparency in inventory management. Practical implications of this research include recommendations for optimizing existing information systems, strengthening internal oversight, and enhancing compliance with established inventory control procedures.